DEFORMITY CORRECTION IN SEVERE ANKYLOSING_x000D_ SPONDYLITIS WITH COMBINED OSTEOTOMIES - (:unkn) unknown (My University, 2020)
Objective: To evaluate the effects of single-level lumbar decancellation osteotomy combined with multiple level polysegmental posteriorosteotomies involving the whole thoracal spine in severe ankylosing spondylitis.Materials and Methods: Between 2008 and 2017, 14 patients (12 men and two women) were included in the study. The indication for surgerywas a progressive loss of horizontal sight due to whole spine kyphosis (chin-brow angle over 90°). The mean age at the time of operation was47 years. Preoperatively and postoperatively, the cobb angle was measured on standing lateral radiographs of the whole spine. The chin-browangle correction was recorded.Results: The mean surgical time was 281 minutes, and the average blood loss was 1870 mL. Preoperative mean chin-brow angle was 97.5°.Postoperative chin-brow angle was 18° (p<0.0001). The preoperative mean thoracic cobb angle was 69°, and the postoperative thoracic cobbangle was 37.5° (p<0.0001). The preoperative mean lumbar lordosis angle was -1.2°, and the postoperative mean lumbar lordosis angle was-29° (p<0.0001). There were no major perioperative and postoperative complications. Two patients had minor wound healing problems. Bonehealing was satisfactory in all patients. Three patients had a loss of correction in thoracal regions of 5, 7, and 8 degrees at the final follow-up visit.Reduction losses were acceptable, and we did not plan any revision surgeries.Conclusion: Our study showed that this surgical method is as effective as two-level lumbar osteotomies used in severe cases and is also a saferprocedure as the latter.